Prehypertension in dyslipidemic individuals; relationship to metabolic parameters and intima-media thickness - Karasek, David; Vaverkova, Helena; Halenka, Milan; Jackuliakova, Dagmar; Frysak, Zdenek; Orsag, Jiri; Novotny, Dalibor (Biomedical papers, 2013)
Introduction: Like hypertension, prehypertension is associated with cardiovascular disease.Aims: The aim of this study was to evaluate: a) the prevalence of prehypertension/hypertension in individuals with various dyslipidemic phenotypes; b) the relation between blood pressure (BP) and other risk factors for atherosclerosis; c) atherogenic potential of prehypertension by the assessment of intima-media thickness of the arteria carotis communis (IMT).Methods: 667 clinically asymptomatic subjects were divided into four dyslipidemic phenotypes (DLP) according to apolipoprotein B (apoB) and triglycerides (TG): DLP1 (n=198, normo-apoB/normo-TG), DLP2 (n=179, normo-apoB/hyper-TG), DLP3 (n=87, hyper-apoB/normo-TG), DLP4 (n=203, hyper-apoB/hyper-TG). DLP1 served as a control group.Results: There was significantly higher prevalence of prehypertension and hypertension in subjects with dyslipidemia (DLP2 43.0%, 41.3%; DLP3 42.5%, 29.9%; DLP4 42.4%, 47.8%) than in normolipidemic individuals (DLP1 32.8%, 20.2%). Systolic and diastolic blood pressure (SBP + DBP) correlated with age, total cholesterol, TG, non-HDL-cholesterol, body mass index and waist circumference; SBP additionally with C-peptide, fasting glycemia; DBP additionally with apoB, homeostasis model assessment (HOMA) and plasminogen activator inhibitor-1. The IMT of hypertensive and of prehypertensive subjects was higher than that of subjects with normal BP in all DLPs.Conclusions: The prevalence of prehypertension was higher in all dyslipidemic patients. The common prevalence of prehypertension/hypertension was highest in the hypertriglyceridemic subjects. Prehypertensive and hypertensive patients had higher IMT than normotensive individuals in all DLPs.
Keywords: prehypertension; hypertension; dyslipidemia; insulin resistance; intima-media thickness